Preventive Measures and Actions of the Police of the Czech Republic against Urban Violence - Martin Hrinko (Communications - Scientific letters of the University of Zilina, 2011)
The following article addresses the current problem of urban violence. The aim of the article is to outline the different preventive measures and actions of the Police of the Czech Republic taken in order to prevent urban violence. Moreover, various ways of documentation of illegal acts are presented. Having been the officer in charge during operations conducted against urban violence, the author also shares his practical experience.